2018
DOI: 10.1108/ijpsm-01-2017-0024
|View full text |Cite
|
Sign up to set email alerts
|

Motives of mergers and acquisitions in the European public utilities

Abstract: Purpose The purpose of this paper is to investigate the motivation and post-merger operating performance (OP) of European utility sectors following mergers and acquisitions (M&A). Design/methodology/approach Motives behind M&A are examined by looking into the relationships between total gains, target gains and acquirer gains. Post-merger OP is measured by comparing the sample of European utilities with a matched portfolio based on size and market to book ratio with respect to five accounting indicato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Grashuis (2018) presents per the results, variability in the financial performance of US farmer cooperatives is for the most part associated with the operating profit margin, which confirms prior findings of cost inefficiency in the empirical literature, therefore, US farmer cooperatives may improve financial performance by emphasizing sales and operating costs. Brahma et al (2018) found that post-merger operating performance is negative and significant across all the five accounting indicators matched by size, and market to book ratio suggesting that utility mergers underperform in the long term, and the findings suggest that gains accruing to utilities involved in acquisitions are short term in nature. Bougatef & Korbi (2018) present the existence of two common determinants of intermediation margins in Islamic and conventional banking systems, and the degree of diversification permits banks to operate with lower margins and exploit the revenue from non-traditional activities to compensate the decrease in intermediation margin, and finally the degree of risk aversion is among the principal factors responsible for the increase of bank margins.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Grashuis (2018) presents per the results, variability in the financial performance of US farmer cooperatives is for the most part associated with the operating profit margin, which confirms prior findings of cost inefficiency in the empirical literature, therefore, US farmer cooperatives may improve financial performance by emphasizing sales and operating costs. Brahma et al (2018) found that post-merger operating performance is negative and significant across all the five accounting indicators matched by size, and market to book ratio suggesting that utility mergers underperform in the long term, and the findings suggest that gains accruing to utilities involved in acquisitions are short term in nature. Bougatef & Korbi (2018) present the existence of two common determinants of intermediation margins in Islamic and conventional banking systems, and the degree of diversification permits banks to operate with lower margins and exploit the revenue from non-traditional activities to compensate the decrease in intermediation margin, and finally the degree of risk aversion is among the principal factors responsible for the increase of bank margins.…”
Section: Literature Reviewmentioning
confidence: 88%
“…In addition, the abstracts suggest that only a very small number of texts handle municipal real estate assets as one holistic portfolio. Researchers tend to prefer individual buildings [29] or sub-portfolios composed of the same type, such as the housing sector [30], office market [9], public utilities [31], heritage [32] etc.…”
Section: Abstractsmentioning
confidence: 99%
“…Synergy can occur when two or more parties collaborate in business to create new value, allowing companies to optimize management and operations for greater effectiveness and efficiency, thereby increasing corporate profits and preventing value destruction (Bradt & Pritchett, 2022;Brahma et al, 2018). The effectiveness resulting from the synergy of M&A can manifest in securing the source of production raw materials for the company, and it can also lead to a decrease in variable costs for the company as a result of synergy with subsidiary companies (Gudmundsson et al, 2020;Kwilinski, 2020).…”
Section: Synergy From Merger and Acquisitionmentioning
confidence: 99%